Unified Modeling Language Website-Based Mail Administration System - Eka Putra (Proceedings of The International Conference on Computer Science, Engineering, Social Science, and Multi-Disciplinary Studies, 2025)
Mail management is one of the administrative activities that plays an important role in maintaining smooth communication and documentation in an organization. However, many agencies still use manual methodsin recording, distribution, and storing letters, so there are often obstacles such as process delays, recording errors, and difficulties in tracing archives. This research aims to design a website-based mail administration system as a solution to improve the effectiveness and efficiency of the mail management process. The design method uses Unified Modeling Language (UML) to model functional needs and process flows in a structured manner through use case, activity, sequence, and class diagrams. The results of the design show that the proposed system is ableto provide a more organized, accessible, and well-documented mail management mechanism. With UML modeling support, system designs become clearer, standardized, and easier to develop. This research is expected to be the basis for the implementation of a digital mail administration system that supports the improvement of the qualityof administrative services in various institutions.